Financial Markets with Trade on Risk and Return - Smith, Kevin (Review of Financial Studies, 2019)
Abstract In this paper, I develop a model in which risk-averse investors possess private information regarding both a stock’s expected payoff and its risk. These investors trade in the stock and a derivative whose payoff is driven by the stock’s risk. In equilibrium, the derivative is used to speculate on the stock’s risk and to hedge against adverse fluctuations in the stock’s risk. I analyze the derivative price and variance risk premium that arise in this equilibrium and their predictive power for stock returns. Finally, I examine the relationship between prices and trading volume in the stock and derivative. Received July 31, 2017; editorial decision December 3, 2018 by Editor Stijn Van Nieuwerburgh. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.